MEDICAL AND SOCIAL ASPECTS OF INDUCED ABORTION IN THE REPUBLIC OF DAGESTAN - Aziza G. Gasangadzhieva; Patimat I. Gabibova; Gyulnara M. Nakhibasheva; Elmira M. Medzhidov; Zaira E. Abdullaeva; Simurden M. Nakhibashev; Maryam M. Medzhidova (Юг России: экология, развитие, 2018)
Aim. The aim of the research is to consider the medical and social aspects of artificially terminating pregnancy in the Republic of Dagestan. Material and methods. To achieve this goal, we have created a database of the cases of artificial abortion in the Republic of Dagestan. Statistical processing of the results of the study was carried out using software packages like STATISTICA and Excel. Results. The total number of abortions for the study period was 157526 cases, of which 26% of cases were spontaneous abortions, 8.9% of cases were abortions for medical reasons. During the period under review, there was an increase in the number of spontaneous abortions and abortions due to medical indications by 170% and 108.6%, respectively. There is the prevalence of abortions of the pregnancy of up to 12 weekperiod, including mini-abortions, the average percentage of the total number of abortions for the study period was 90%. In the Republic of Dagestan, the average annual intensive standardized abortion rate was 14.67 cases per 1,000 women of childbearing age women of childbearing age (WCA). And among the urban population, this number is higher, and amounted to 25.57 ‰ against 6.25 ‰ in rural areas. The highest values of the average long-term intensive frequency of abortions are observed in the cities of Kizilyurt, Derbent, Makhachkala, Kaspiisk; in the countrysides: Dakhadayevsky, Tarumovsky, Laksky and Babaurtovsky districts. Conclusion. The problem of abortion, despite the steady tendency to reduce their number, still needs to be solved because it is the leading cause of maternal death in Russia, inflammatory diseases of the genitals, infertility, and it also adversely affects the course of subsequent pregnancies and births, increasing the frequency miscarriage, maternal and perinatal pathology.